2017
DOI: 10.1038/oncsis.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

CRB3 downregulation confers breast cancer stem cell traits through TAZ/β-catenin

Abstract: The cancer stem cell (CSC) theory depicts a special population within the cancer mass that self-renew and sustain the cancer, even if the other cells were eliminated by therapies. How CSCs acquire these unique traits is still unclear. Crumbs homolog 3 (CRB3), a member of the CRB polarity complex, has been reported to act as a tumor suppressor. Here, we detected significantly lower or negative CRB3 expression in human breast cancer tissues. Knockdown of CRB3 generated non-tumorigenic, immortalized breast epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…However, tamoxifen resistance has become a roadblock for successful treatment and caused the failure of tamoxifen‐related therapy. Our previous study found that decreased CRB3 expression led to the acquirement of cancer stem cell‐like properties in non‐tumorigenic, immortalized breast epithelial cell line MCF 10A . Thus, the current study has been suggested that increased expression of cell polarity protein CRB3 might inhibit stemness characteristics of breast cancer that in turn overcomes tamoxifen resistance.…”
Section: Discussionsupporting
confidence: 52%
“…However, tamoxifen resistance has become a roadblock for successful treatment and caused the failure of tamoxifen‐related therapy. Our previous study found that decreased CRB3 expression led to the acquirement of cancer stem cell‐like properties in non‐tumorigenic, immortalized breast epithelial cell line MCF 10A . Thus, the current study has been suggested that increased expression of cell polarity protein CRB3 might inhibit stemness characteristics of breast cancer that in turn overcomes tamoxifen resistance.…”
Section: Discussionsupporting
confidence: 52%
“…In the current study, we found that CRB3 expression was inversely associated with tumour size (Table ), which is consistent with previous studies showing that downregulation of CRB3 expression induced breast cancer cell proliferation, whereas CRB3 overexpression inhibited proliferation of human breast cell lines . Our previous study also showed that the downregulation of CRB3 expression increased migration and invasion of breast cancer cells, whereas CRB3 overexpression inhibited migration and invasion of human breast and kidney cancer cell lines .…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study revealed that CRB3 expression was lower in breast cancer compared with that of normal mammary gland tissues. 20 In this study, we detected CRB3 expression in 192 invasive human breast cancers (Table 1) immunohistochemically. The data showed that CRB3 protein was expressed in 65/192 (33.8%) cases of the cytoplasm of tumour cells ( Figure 1).…”
Section: Association Of Crb3 Protein Expression With Tnbcmentioning
confidence: 77%
See 2 more Smart Citations